A Clinicopathological Study of Malignant Insulinoma in a Contemporary Series. Issue 1 (January 2017) - Yu, Run; Nissen, Nicholas N.; Hendifar, Andrew; Tang, Laura; Song, Yu-Li; Chen, Yuan-Jia; Fan, Xuemo
Abstract : Objective: The aim of the study was to address the origin and natural history of malignant insulinoma. Methods: Retrospective review of medical records of patients diagnosed with insulinoma at Cedars-Sinai Medical Center between 2000 and 2015 was conducted. Hormonal expression in tumor specimens was examined by immunostaining. Results: All the 9 patients with malignant insulinoma (35% of 26 patients with insulinoma) already had liver metastasis at hypoglycemia presentation with bulky cumulative tumor burden. Six patients had de novo diagnosis, 2 had known metastatic nonfunctioning pancreatic neuroendocrine tumor, and 1 had a known pancreatic mass. Tumor grade at presentation was G1 in 4 patients, G2 in 4, and unknown in 1. Four patients died 2 to 32 months after presentation, all with extensive liver tumor involvement. Tumor expression of proinsulin and insulin was heterogeneous and overall infrequent. The proinsulin levels and proinsulin/insulin molar ratio in patients with malignant versus benign insulinoma were 334 versus 44 pmol/L and 2.1 versus 0.9, respectively. Conclusions: Malignant insulinoma seems to arise from and behave like nonfunctioning pancreatic neuroendocrine tumor oncologically but with metachronous hyperinsulinemic hypoglycemia. High proinsulin levels and proinsulin/insulin molar ratio may suggest malignant insulinoma.